REKAM MEDIS ELEKTRONIK (RME) UNTUK PELAYANAN GIZI RUMAH SAKIT - Diah Ayu Ratnaningsih; Guardian Yoki Sanjaya; Adhiyanti Asikin (Journal of Health Service Management, 2023)
Background: Electronic Medical Record (EMR) is mandatory for the healthcare provider in Indonesia. EMR were also developed for medical support services such as nutrition services. EMR application for nutrition services consists of nutrition assessment forms and patient-integrated clinical development records.Objective: To determine factors that influence the implementation of EMR for hospital nutrition services.Methods: This research is qualitative research with a single-case holistic design. The research location was in Instalasi Gizi RSUD Dr. Soetomo, from May to June 2023. The data collecting method was using in depth-interview and focus group discussions. Participants were selected using purposive sampling. Data was analyzed based on the Human, Organization, and Technology (HOT)–Fit Framework.Results: This research showed that the main factor influencing the success of EMR implementation for hospital nutrition is the digital competencies of the staff. These competencies could be increased by giving some training to the staff. Another essential factor is that organization should support by providing Standard Operating Procedures (SOPs) for EMR implementation and technical support from the Information Technology (IT) team. IT team has the responsibility to handle complaints and problems about EMR. Facilities such as computers and Local Area Networks (LAN) should be sufficient to make EMR implementation run well. The interface and features of EMR should answer the needs of the staff. So, staff would feel EMR is beneficial to help them finish their work, and they would show their acceptance toward this EMR.Conclusions: The success of EMR implementation for hospital nutrition services is determined by several factors like staff digital competencies, organizational support, and provision of computers and LAN for implementing EMR. Positive perception about the benefit of EMR encouraged the increase of EMR utilization in hospitals.